(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Canadian literature has been strongly influenced by the international immigration ,particularly in recent decades . Since before European contact and the confederation of Canada, indigenous people in North America have occupied Canada and have maintained a rich and diverse history of culture, identity, language, art and literature. Shields works mainly focused on the existential aspects and individual manner. The Republic of Love is no exception it speaks about the subject of love is treated with pure romanticism nor with and mistrust. Shields was very much aware of fashionably dim view of love taken today. She loved stories that placed lovers in isolation and wanted her pair of lovers firmly in the midst of their community where the networks of family and friends form the real street maps. Shield’s perception of love is a mythical and self oriented. Its arrival cannot be arranged nor its properties deconstructed. This monochromatic aspects intended to be reflected in the occupations of the characters with Fay’s involvement with mermaids intended to accentuate her existence with a mythic quality while Tom’s charisma over the air waves and his impact on other people’s lives is intended to give a magical dimension. A man should resubmit his individuality as much has he can have particular ideas about himself should be elaborated by the logic of self and other aspects. This paper Carol Ann Shields’s The republic of love as a for As A Crave For Invariant and other Aspects, analyzes the possible ways in individuals interact with their communities.